Perbandingan antara Nilai APGAR pada Bayi Prematur dengan Bayi Postmatur di RSUD Temanggung Tahun 2013 - Endah Sulistyowati; Ngadiyono Ngadiyono (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
Infant mortality incidence in Indonesia, 46% died during the BBL(WHO / CHERG, 2010). Causes of perinatal mortality are congenital abnormalities, prematurity, birth trauma, infection, fetal distress and neonatal asphyxia. Premaur and postmature baby more prone to problems that cause neonatal mortality. Such as asphyxia which can be assessed with the Apgar score. The purpose of this research is to determine the ratio between Apgar score postmature premature infants and infants at Waterford Regional Hospital 2013. Penelitian year was conducted at Waterford Regional Hospital, using a cross-sectional survey. The population in this study were pregnant women trimester II and III examination at Waterford Regional Hospital. Sampling technique used was nonprobability sampling with purposive sampling technique. The research was done by observation with a check list. The results showed no differences between preterm infants with Apgar scores post-mature infants with p value of 0.001 ≤ α 0.05 in the first minute, five-minute p value 0.006 ≤ α 0.05 and p value ≤ α tenth minute 0.001 0.05 this means that Ho is rejected and Ha accepted where it can be concluded no difference in the value of Apgar scores of babies born premature babies born with postmature the first minutes,fifth and tenth. From these results it is expected that Should a health care provider can immediately detect the presence of gravity of the fetus while still in the womb, so that patients can get help faster